New Records of Butterflies (Lepidopetra :Insecta) of Azmat Abad Village of Thanna Mandi District Rajouri of Jammu and Kashmir - Sajid Ali; Pragya Shrivastava (Research Parks Publishing LLC, 2021)
The present communication is based on the sighting of five new species of butterflies viz recorded first time in Azmat Abad Village and ThannaMandi District Rajouri Jammu and Kashmir, based on the field survey. The Butterflies recorded the first time in Azmat Abad village and ThannamandiViz (Junoniaiphita) Chocalate pansy, (Pieriscanidia) Indian cabbage white, (Fabriciananadippe)High brown fritillary, (Aglaiscaschmirensis)Indian tortoiseshell. The Altitude is 1668 meters above the sea level support sub-tropical to temperate vegetation and offers congenial climatic condition favorable for growth of vegetation including fauna. Altitude distribution of butterflies from higher to lower altitudes. With an altitudes ranges number of species present in lower altitudes and keep decreasing toward higher altitude .The present study added valuable information on diversity of butterfly fauna and will contribute in developing effective conservation in Azmat Abad village and ThannaMandi District Rajouri of Jammu and Kashmir.